Ficus erecta Thunb. Leaves Ameliorate Cognitive Deficit and Neuronal Damage in a Mouse Model of Amyloid-β-Induced Alzheimer’s Disease - Sohn, Eunjin; Kim, Yu Jin; Kim, Joo-Hwan; Jeong, Soo-Jin (Frontiers in Pharmacology, 2021)
Alzheimer’s disease (AD) pathogenesis is linked to amyloid plaque accumulation, neuronal loss, and brain inflammation. Ficus erecta Thunb. is a food and medicinal plant used to treat inflammatory diseases. Here, we investigated the neuroprotective effects of F. erecta Thunb. against cognitive deficit and neuronal damage in a mouse model of amyloid-β (Aβ)-induced AD. First, we confirmed the inhibitory effects of ethanol extracts of F. erecta (EEFE) leaves on Aβ aggregation in vivo and in vitro. Next, behavioral tests (passive avoidance task and Morris water maze test) revealed EEFE markedly improved cognitive impairment in Aβ-injected mice. Furthermore, EEFE reduced neuronal loss and the expression of neuronal nuclei (NeuN), a neuronal marker, in brain tissues of Aβ-injected mice. EEFE significantly reversed Aβ-induced suppression of cAMP response element-binding protein (CREB) phosphorylation and brain-derived neurotrophic factor (BDNF) expression, indicating neuroprotection was mediated by the CREB/BDNF signaling. Moreover, EEFE significantly suppressed the inflammatory cytokines interleukin 1beta (IL-1β) and tumor necrosis factor alpha (TNF-α), and expression of ionized calcium-binding adaptor molecule 1 (Iba-1), a marker of microglial activation, in brain tissues of Aβ-injected mice, suggesting anti-neuroinflammatory effects. Taken together, EEFE protects against cognitive deficit and neuronal damage in AD-like mice via activation of the CREB/BDNF signaling and upregulation of the inflammatory cytokines.